2011
DOI: 10.3944/aott.2011.2497
|View full text |Cite
|
Sign up to set email alerts
|

A new index for the assessment of distal radius fractures involving the ulnar styloid

Abstract: Our results suggested that the RSI can be used as a predictor of the clinical outcome in patients with distal radius fractures involving the ulnar styloid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…They noted that 78% of ulnar styloid nonunions in a group of 91 patients with ORIF-treated distal radial fracture and ulnar styloid avulsion exhibited similar clinical outcome compared with those with an ulnar styloid fracture union. Seventeen of 44 patients who developed an ulnar styloid nonunion in a study by Orhun et al (2011) showed no differences in clinical outcomes compared with those with a united healed ulnar styloid fracture.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…They noted that 78% of ulnar styloid nonunions in a group of 91 patients with ORIF-treated distal radial fracture and ulnar styloid avulsion exhibited similar clinical outcome compared with those with an ulnar styloid fracture union. Seventeen of 44 patients who developed an ulnar styloid nonunion in a study by Orhun et al (2011) showed no differences in clinical outcomes compared with those with a united healed ulnar styloid fracture.…”
Section: Discussionmentioning
confidence: 93%
“…Dislocation of the ulnar styloid as it pertains to the clinical outcome was investigated by Orhun et al (2011) in 44 combined distal radial and ulnar styloid fractures. They found that ulnar styloid displacement exerted a negative effect on both Gartland and Werley scores (Gartland and Werley, 1951) and upon the radiological result according to Steward’s radiological scoring method (Stewart et al, 1985) at a mean follow-up of 18 weeks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These injuries are often managed non-operatively, even when open reduction and internal fixation of the distal radial fracture is carried out. Although some clinical studies suggest concomitant ulnar styloid fractures lead to reduced wrist functional outcomes and distal radioulnar joint (DRUJ) instability (Amorosa et al., 2011; Belloti et al., 2010; May et al., 2002; Orhun, 2011; Oskarsson et al., 1997; Pidgeon et al., 2017), others have reported no effect on patient-reported outcomes, even when there is nonunion (Buijze and Ring, 2010; Kazemian et al., 2011; Kim et al., 2010, 2011; Sammer et al., 2009; Souer et al., 2009; Wijffels and Ring, 2016; Wijffels et al., 2014; Zenke et al., 2009). Discrepancy between these studies may stem from a lack of discrimination between ulnar styloid fractures that incorporate the fovea and those that do not (Wijffels et al., 2014).…”
Section: Introductionmentioning
confidence: 99%